Labial Gland Mesenchymal Stem Cell Derived Exosomes-Mediated miRNA-125b Attenuates Experimental Sjogren’s Syndrome by Targeting PRDM1 and Suppressing Plasma Cells - Xing, Yixiao; Li, Boya; He, Jing; Hua, Hong (Frontiers in Immunology, 2022)
The pathogenesis of the prototypical chronic autoimmune disorder primary Sjögren syndrome (pSS) has been thought to be B-cell-centric, based on serum autoantibodies, the increased risk of B cell lymphoma, and altered B cell subsets in patients with pSS. Over the last 10 years, therapies targeting B cells have been investigated for pSS; however, current evidence for the efficacy of B cell targeted therapies in pSS is still sparse. Mesenchymal stem cells (MSCs) might represent a promising strategy for cell therapy of autoimmune diseases via regulation of immune cells. MSC-released exosomes carry various bioactive molecules and thus have been studied in MSC-based therapy. The newly discovered labial gland MSCs (LGMSCs) have exhibited enhanced performance. Herein, we aimed to determine the effects of LGMSC-derived exosomes (LGMSC Exos) on the symptoms of a mouse model of pSS and their regulatory effect and mechanism on B cell subsets. In vivo, treatment of the spontaneous mouse model of pSS with LGMSC-Exos resulted in reduced inflammatory infiltration and restored saliva secretion in salivary glands. In vitro, coculture of LGMSC-Exos with peripheral blood mononuclear cells of patients with pSS markedly reduced the proportions of CD19+CD20-CD27+CD38+ plasma cells among peripheral blood mononuclear cells. Further investigations provided evidence that LGMSC-Exo-derived microRNA-125b affected plasma cells of pSS by directly binding to its target gene, PRDM1 (PR domain zinc finger protein 1, also known as BLIMP1), which might be developed as a target to treat pSS. Overall, these findings provided a possible exploitable therapeutic target in pSS and provide new insights into the potential therapeutic application of exosomes in pSS and other disease mediated by B-cells.